The effective detoxification of blood plasma by foam bubbling - M. A. Khachaturyan; Yu. A. Ershov (Сеченовский вестник, 2014)
A blood plasma detoxitycation efficiency by a barbotage method (gas bubbling through a liquid medium) is investigated. It is established that the efficiency of removal of carbon tetrachloride out of the plasma and its mixtures with plasma substitutes is determined by the speed of gas bubbling and foam characteristics such as fluid-time foam formation and concentration of foaming agent.